"I know how it is when nobody sees you": oral-history performance methods for staging trauma. Issue 2 (2nd April 2020) - Yeboah, Nikki Owusu
ABSTRACT: In this essay, I argue that, in a society oversaturated with images and narratives of racial trauma, creating theatre for social change requires more than staging minoritarian bodies with the aim of making their trauma visible. Contemporary oral-history performance practitioners must face the challenge of how to make the hypervisible meaningful. Drawing on my own production The (M)others, an oral-history performance adapted from the narratives of Bay-Area women who have lost family members to police violence, I present a methodology that works to disrupt the ways contemporary audiences are invited to passively consume, rather than actively intervene in, acts of racial trauma.